Interactive case vignettes utilizing simulated pathologist-clinician encounters with whole slide imaging and video tutorials of whole slide scans improves student understanding of disease processes - Adam J Horn; Donna Czarnecki; Subodh M Lele (Elsevier, 2012)
Background: One of the drawbacks of studying pathology in the second year of medical school in a classroom setting is the relatively limited exposure to patient encounters/clinical rotations, making it difficult to understand and fully appreciate the significance of the course material, specifically the molecular and tissue aspects of disease. In this study, we determined if case vignettes incorporating pathologist-clinician encounters with whole slide imaging (WSI) and narrated/annotated videos of whole slide (WS) scans in addition to clinical data improved student understanding of pathologic disease processes. Materials and Methods: Case vignettes were created for several genitourinary disease processes that utilized clinical data including narratives of pathologist-clinician encounters, WSI, and annotated video tutorials of WS scans (designed to simulate "double-heading"). The students were encouraged to view the virtual slide first, with the video tutorials being provided to offer additional assistance. The case vignettes were created to be interactive with a detailed explanation of each correct and incorrect question choice. The cases were made available to all second year medical students via a website and could be viewed only after completing a 10 question pre-test. A post-test could be completed after viewing all cases followed by a brief satisfaction survey. Results: Ninety-six students completed the pre-test with an average score of 7.7/10. Fifty-seven students completed the post-test with an average score of 9.4/10. Thirty-six students completed the satisfaction survey. 94% agreed or strongly agreed that this was a useful exercise and 91% felt that it helped them better understand the topics. Conclusion: The development of interactive case vignettes incorporating simulated pathologist-clinician encounters with WSI and video tutorials of WS scans helps to improve student enthusiasm to learn and grasp pathologic aspects of disease processes that lead to clinical therapeutic decision making.